Potential oral wound healing of topical application of dental gel prepared from Baccaurea angulata fruit in diabetic rats - Abdul Rahman, Mohammad Nasrin; Sukmasari, Susi; Doolaanea, Abd Almonem; Abdul Qader, Omar Abdul Jabbar (Pharmainfo Publications, 2018)
Objective: This study investigates the effect of Baccaurea angulata fruit extract towards wound healing activity at tooth extractions sites. Significance: High antioxidant content in underutilised Baccaurea angulata were expected to open up new possibilities for tooth extraction procedure among diabetic patients. Methods: Sprague dawley rats were divided into 6 groups, and l their left mandibular first molar tooth were extracted. The alveolar socket were treated accordingly where group 1, 2, 3, 4, and 5 were diabetic rats (induced using Streptozotocin) applied with plain gel, alveolex, 3%, 5%, and 10% Baccaurea angulata extract respectively. Group 6 were non diabetic rats applied with plain gel. On day 4, 7 and 18, rats were euthanized, and the tissue samples were processed for histomorphological analysis. Results: It was found that Baccaurea angulata does significantly promotes tooth extraction wound healing in diabetic rats comparable to diabetic group treated with alveolex and non-diabetic rats at early phase of the wound. However the positive effect were not obvious at day 7, while at day 18, groups treated with Baccaurea angulata treated group had higher mean scores in most categories although may not statistically significant different. BADG concentration of 4% was found to give the best effects on wound healing. Conclusion: To a certain extent, Baccaurea angulata extract does promotes tooth extraction wound healing in diabetic rats.